Modeling Multispecies Gene Flow Dynamics Reveals the Unique Roles of Different Horizontal Gene Transfer Mechanisms - Nazarian, Phillip; Tran, Frances; Boedicker, James Q. (Frontiers in Microbiology, 2018)
Horizontal gene transfer within diverse bacterial populations occurs through multiple mechanisms of exchange. The most established routes of gene transfer, transduction, transformation, and conjugation, have been characterized in detail, revealing the advantages and limitations of each mechanism. More recently, interspecies gene exchange via extracellular vesicles has been reported and characterized, making vesicle-mediated exchange a fourth, general mechanism of gene transfer. Despite an understanding of each individual pathway, how all of these mechanisms act in concert has not been explored. Here we develop a model of gene exchange in a multispecies bacterial community that takes into account the rates and limitations of all four gene transfer mechanisms. Our results reveal unique roles for each gene exchange mechanism, and highlight how multiple pathways working together are required for widespread gene exchange within diverse bacterial populations.